KESAN PENAMBAHAN MINYAK KELAPA DARA ATAU EKSTRAK ALOE VERA DALAM MENINGKATKAN AKTIVITI ANTIVIRUS IN VITRO GONIOTHALAMIN: THE EFFECTS OF THE ADDITION OF VIRGIN COCONUT OIL OR ALOE VERA EXTRACT IN INCREASING IN VITRO ANTI-HHV-1 ACTIVITY OF GONIOTHALAMIN - IBRAHIM, NAZLINA; TAI, JIA HUI; YIP, CHEE WAI; MD NOR, NOREFRINA SHAFINAZ (Malaysian Applied Biology, 2022)
The antiviral activity of goniothalamin (GTN) from Goniothalamus umbrosus root, virgin coconut oil (VCO) and aloe vera extract (AVE) have been reported, but the combined activity is yet to be determined. This study aims to determine the stability, cytotoxicity and effectiveness of pure GTN, combination of GTN and VCO (GTN+VCO) or combination of GTN and AVE (GTN+ AVE) towards in vitro Human Herpesvirus 1 (HHV-1) infection. GTN stability improved significantly (α<0.05) when added with VCO or AVE even though reduction in concentration was noted. The CC50 values for GTN towards vero cells increased when combined with VCO or AVE, which generally reduces the cytotoxicity. Antiviral activity determination by plaque reduction assay in vero cells showed increase in EC50 values with reference to GTN concentration. Selective index (SI) values for pure GTN (11.94), GTN+VCO (12.23), and GTN+AVE (25.73) respectively. The mode of antiviral activity for all three test substances was post-treatment essentially more effective when treated 2 hours post-infection to cells. The test substances did not protect cells from virus infection if pre-treated and was not virucidal. In conclusion, AVE stabilises GTN in solution and GTN+AVE improves the anti-HHV-1 activity worth for further examination as plant-based antiviral agent.